Role of the evaluation process of the staff in determining the training programs Field research in the Office of the Inspector General of the Ministry of Health / Iraq - عبد, ناظم جواد; عبد الحسين, اركان زهير (Journal of Economics and Administrative Sciences, 2018)
The objective of this research is to determine the relationship between the performance evaluation process and the training programs for the employees, to identify the extent of the organization's commitment to perform the performance evaluation process for its employees and to use the results of this process in determining the appropriate training programs. Performance evaluation, functional analysis, evaluation method used, dependent variable (training programs) and its dimensions, type of programs, program objectives, program curriculum, And the application of the field research methodology and the questionnaire, which included 146 individuals to know their views and analyze them statistically according to the Likert scale and using several tools (arithmetic mean, standard deviation, ratios, frequencies, coefficient of interpretation, regression coefficient, The coefficient of ß, the value of F, the value of P,and the program (Spss) and the program (Excel) to reach the researchers to a set of conclusions most important not to adopt the Office of the Inspector General on the results of performance evaluation in the identification of its training programs, In this way, the organization in question must activate the results of the performance assessment process in determining the land Mug training for workers and compatible with their performance and the amount of skills and experience to enjoy consistent with their aspirations and achieve their goal levels.